In situ decoration of laser-scribed graphene with TiO2 nanoparticles for scalable high-performance micro-supercapacitors. (May 2021) - Fornasini, Laura; Scaravonati, Silvio; Magnani, Giacomo; Morenghi, Alberto; Sidoli, Michele; Bersani, Danilo; Bertoni, Giovanni; Aversa, Lucrezia; Verucchi, Roberto; Riccò, Mauro; Lottici, Pier Paolo; Pontiroli, Daniele
Abstract: Graphene-based miniaturized supercapacitors, obtained via laser conversion of suitable precursors, have been attracting recent attention for the production of energy storage small-scale devices. In this work, a one-pot synthesis of TiO2 nanoparticles embedded in porous graphene-based electrodes has been obtained with the LightScribe® technology, by converting the precursor materials through the absorption of a DVD burner infrared laser light. Enhanced electrochemical performance of devices has been achieved thanks to the combination of faradic surface reactions, arising from metal oxide nanoparticles, with the conventional electrochemical double layer capacitance, arising from porous graphene. Micro-supercapacitors, consisting of TiO2 -graphene electrodes, have been tested by investigating two hydrogel polymer electrolytes, based on polyvinyl alcohol/H3 PO4 and polyvinyl alcohol/H2 SO4, respectively. Specific areal capacitance up to 9.9 mF/cm 2 are obtained in TiO2 -graphene devices, corresponding to a volumetric capacitance of 13 F/cm 3 and doubling the pristine graphene-based device results. The micro-supercapacitors achieved specific areal energy and specific areal power of 0.22 μWh/cm 2 and 39 μW/cm 2, along with a cyclability greater than 3000 cycles. These high-performance results suggest laser-scribed TiO2 -graphene nanostructures as remarkable candidates in micro-supercapacitors for environment-friendly, large-scale and low-cost applications. Graphical abstract: Image 1 Highlights: Novel interdigitated TiO2 decorated graphene microsupercapacitors are prepared. One-pot synthesis of graphene and TiO2 nanoparticles via LightScribe® technique. Combined effect of electrical double layer and faradic capacitance is observed.